TO UNITE OR NOT TO UNITE? A CASE STUDY OF PRESBYTERIANISM IN SOUTH AFRICA, 1897-1923 - Duncan, G A (Acta Theologica, 2018)
As from 1891, attempts to bring all Presbyterians of Scottish and Scottish mission descent in South Africa together into one church faced insuperable barriers. Their histories and traditions, as well as their demographic and ethnic composition were all issues, despite their similarities. The Presbyterian Church of South Africa was formed in 1897, and the Bantu Presbyterian Church of South Africa in 1923. Discussions on various forms of relationship started in 1891 and continued in the years following the formation of the Bantu Presbyterian Church in South Africa. This article investigates the issues at stake in the attempts to establish one Presbyterian denomination from the disparate Scottish ecclesiastical bodies, using primary and secondary sources and focusing mainly on the issue of racism.